2020
DOI: 10.21203/rs.3.rs-20407/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular vesicles from  deciduous pulp stem cells recover bone loss by regulating telomerase activity in an osteoporosis mouse model

Abstract: Background: Systemic transplantation of stem cells from human exfoliated deciduous teeth (SHED) induces bone regeneration in animal models of osteoporosis; however, the mechanisms underlying this remain unclear. Here, we hypothesized that trophic factors within SHED-releasing extracellular vesicles (SHED-EVs) rescue osteoporotic phenotype.Methods: EVs were isolated from culture supernatant of SHED. SHED-EVs were treated with or without ribonuclease and systemically administrated into ovariectomized mice, follo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…SHED-releasing EVs (SHED-EVs) participate in intercellular communication to exert therapeutic effects via bioactive molecules, such as proteins and miRNAs, in acute inflammation, brain injury, and Parkinson disease (2123). Our study showed that SHED-EVcontaining RNA rescued the telomerase activity of recipient BMMSCs in estrogen-deficient mice, leading to the suppression of bone resorption through an improved osteoblastic function in recipient BMMSCs (24). However, whether SHED-EVs participate in the treatment of SLE and their potential mechanism of action have not yet to be elucidated.…”
Section: Targeting Of Deciduous Tooth Pulp Stem Cellderived Extracell...mentioning
confidence: 80%
See 1 more Smart Citation
“…SHED-releasing EVs (SHED-EVs) participate in intercellular communication to exert therapeutic effects via bioactive molecules, such as proteins and miRNAs, in acute inflammation, brain injury, and Parkinson disease (2123). Our study showed that SHED-EVcontaining RNA rescued the telomerase activity of recipient BMMSCs in estrogen-deficient mice, leading to the suppression of bone resorption through an improved osteoblastic function in recipient BMMSCs (24). However, whether SHED-EVs participate in the treatment of SLE and their potential mechanism of action have not yet to be elucidated.…”
Section: Targeting Of Deciduous Tooth Pulp Stem Cellderived Extracell...mentioning
confidence: 80%
“…Given that the frequency of engrafted SHED is not significant in the BM of MRL/lpr mice (3,24), we hypothesized that indirect communication of donor SHED is involved in the rescue of BMMSC functions in MRL/lpr mice. We focused on EVs because diverse trophic factors within MSC-releasing EVs are known to contribute to cellcell communication in MSC-based therapy (29,30).…”
Section: Systemic Administration Of Shed-evs Rescued Sle-like Disorde...mentioning
confidence: 99%
“…The reasons why SHED-Heps exhibit the short-term survival and engraftment in the recipient animals are considered due to the immature hepatic differentiation and immunogenicity of donor cells, the xenograft system in immunocompetent animals without any immunosuppressive drug, and the chronical cytotoxic condition after transplantation. On the other hand, SHED-secreting trophic factors including cytokines and extracellular vesicle-containing RNA contents affect immunosuppressive functions [43,44]. The effect of stanniocalcin 1 secreted from SHED-Heps is anti-hepatitis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lots of factors regulated by osteoclasts, like Wnt10b, sema3a, smad1/5/8, and so on, had been widely demonstrated to mediate the differentiation and function of osteoblasts [21,40,41].…”
Section: Discussionmentioning
confidence: 99%